Burnout amongst interns in the department of Obstetrics and Gynaecology, University of Witwatersrand - Odine, Peter Odianosene (My University, 2021)
The mental state and wellbeing of a medical trainee or intern determines his or her ability to learn and to discharge his or her responsibilities adequately and responsibly. However, Burnout as a medical condition is often not recognized or sometimes ignored or explained away. Aim/Objective: Therefore, the study describes the prevalence of burnout amongst interns in the Witwatersrand academic hospitals. Method: Hundred and twenty interns who were in their fourth month of internship in the department of Obstetrics and Gynaecology were recruited for the study through the use of convenient sampling technique. Data were collected through the use of a two-part questionnaire. The first part of the questionnaire contained questions on demographics and possible associated factors to burnout while the second part contained questions from the Manslach Burnout Inventory for medical personnel. Data were analyzed through the use of descriptive statistics, student’s T-test, one way ANOVA, Pearson’s correlation and Maslach burnout inventory scale. Results: The results showed that majority (63%) of the interns were female aged 26 years (SD ±2.87) and about 48% drank one form of alcohol or the other. The median work hours was 72 hours spread across 6 days in a week while about 41% had encountered intra uterine death. In addition, poor recruitment was the major stressor of interns (4.14±1.11) while personal accomplishment (32.14 ±9.00) was the highest form of burnout. A positive finding in our circuit was the fact that interns did not find administration to be insensitive to their problems however, the most frequent associated factor for the cause of burnout was inadequate manpower employed to do the job. Conclusion: Thus, the study concluded that accepted methods of militating against burnout include mindful communication, vacation, delegation of duties, moral support to workers, attention to the welfare of workers by health administrators and control of working hours. Therefore the study recommended that management should pay heed to recruitment of more interns in our academic Hospitals and more attention should be paid to recreation and vacation of interns
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine, 2021